Factors rocketing in the price of essential goods in Malaysia / Nor Azira Ismail, Jamilah Laidin and Shahiszan Ismail - Ismail, Nor Azira; Laidin, Jamilah; Ismail, Shahiszan (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2022)
The current skyrocketing prices on essential goods such as vegetables, poultry, eggs, and other food items when Malaysia has yet to fully recover from the impacts of COVID-19 is such a worrying issue to consumers. Based on a report by the Consumers’ Association of Penang (CAP), the prices of certain vegetables have steeply increased by as much as 200%. These include vegetables such as cauliflower (RM7 to RM16 per kg, choy sum (RM3 to RM9), broccoli (RM8 to RM20), and sawi (RM5 to RM8). Here are a few factors that contribute to the increase in the prices of essential goods in Malaysia.